Monofilament anti-rotational suture combined with TPLO to prevent pivot shift: surgical technique and novel TPLO plate design - von Pfeil, Dirsko J. F.; House, Parker N. (Frontiers in Veterinary Science, 2025)
ObjectivesTo identify dogs at risk of developing pivot-shift (PS) following tibial-plateau-leveling-osteotomy (TPLO) using a rotational-instability-test (RI-test), describe a combination of a monofilament anti-rotational suture (ARS) with TPLO and assess this technique for feasibility, compare post-operative PS-incidence in dogs receiving a standard TPLO (TPLO-only) or a TPLO with ARS (TPLO+ARS), and design a novel TPLO-plate facilitating ARS-anchoring (TPLO/ARS-plate).Study designIn this clinical pilot trial on 85 client-owned dogs and instrumentation design study, the RI-test and ARS-placement-technique were described and performed. Reporting included: anesthesia and surgery times, bone-healing, post-TPLO-PS-incidence, follow-up and complications. Significance was set as p ≤ 0.05. Comprehensive engineering of a novel TPLO plate was performed.ResultsBetween TPLO-only (n = 57) and TPLO+ARS (n = 28) groups, significant differences were found for surgery time (p = 0.01), anesthesia time (p<0.001) and bone healing scores (p = 0.03), all being longer/higher for TPLO+ARS. PS-incidence was 2/57 (TPLO-only) and 0/28 (TPLO+ARS) within the first 8 weeks post-surgery (p = 1.00). Medium follow-up was 642 days. Major complications during that time occurred in 2/57 (TPLO-only; infection and implant removal) and 1/28 (TPLO+ARS; infection, PS-development and implant removal) dogs (p = 1.00). A novel TPLO/ARS-plate was designed.ConclusionPost-TPLO-PS might be reduced following ARS placement. Additional studies are indicated to validate and refine the RI-test and assess the novel TPLO/ARS-plate in the clinical setting.